PENGARUH MOTIVASI KERJA, DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN DENGAN KEPUASAN KERJA SEBAGAI INTERVENING (STUDI PADA SEKRETARIAT DAERAH KABUPATEN PAMEKASAN) - Hengky Arieftian Meirdiansyah; Andi Sularso; Diana Sulianti K. Tobing (RELASI : JURNAL EKONOMI, 2014)
This study aims to determine the effect of work motivation and employee discipline. In addition, this study also used the variable job satisfaction as an intervening variable to analyze the effect of job satisfaction on employee performance in Pamekasan Regional Secretariat. This study is a quantitative  and explanatory research. The sampling technique used proportionate stratified random sampling based on the position/ rank/class. Data obtained by questionnaire respondents are 125 people from 181 people of total population. The analytical method used Structural Equation Modeling (SEM). The results showed that significantly influence the work motivation through job satisfaction performance that is equal to 0.637. While labor discipline also significantly influence performance through job satisfaction of 0.330.